2022
DOI: 10.1002/anie.202109500
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Targeting Circular Aptamer Strategy Enables the Recognition of Different Leukemia Cells with Enhanced Binding Ability

Abstract: Currently, the broad use of monovalent aptamers in oncology faces challenges, including insufficient recognition and internalization caused by a finite number of receptors on the cell surface, as well as a confined recognition spectrum. Herein, we describe the development of a dual‐targeting circular aptamer (DTCA) that can recognize two different biomarkers on living cells to augment aptamer–receptor interactions, thus enhancing recognition of the target cells. This improvement not only boosts binding and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…This strategy dramatically promotes the aptamer capacity of binding MPs on the cell surface, compensating for insufficient recognition and binding of monovalent aptamers. For example, the combined use of sgc8c and other aptamers enables anchoring over 90% of DNA nanoassemblies onto the cell membrane, whereas the anchorage efficiency is only ∼30% using sgc8c alone. , In addition, these aptamers can also be incorporated into cyclic bivalent conjugates with higher biostability and efficiency for transmembrane protein delivery. , These covalently bivalent aptamers, however, commonly rely on dsDNA connectors, making it inconvenient to load and transport nucleic acid cargoes. To address it, here we engineer a G-quadruplex-proximized aptamer (G4PA) nanodevice that more efficiently binds cell-surface transferrin receptor (TfR) and is also capable of conveniently loading cargoes for targeted transmembrane delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy dramatically promotes the aptamer capacity of binding MPs on the cell surface, compensating for insufficient recognition and binding of monovalent aptamers. For example, the combined use of sgc8c and other aptamers enables anchoring over 90% of DNA nanoassemblies onto the cell membrane, whereas the anchorage efficiency is only ∼30% using sgc8c alone. , In addition, these aptamers can also be incorporated into cyclic bivalent conjugates with higher biostability and efficiency for transmembrane protein delivery. , These covalently bivalent aptamers, however, commonly rely on dsDNA connectors, making it inconvenient to load and transport nucleic acid cargoes. To address it, here we engineer a G-quadruplex-proximized aptamer (G4PA) nanodevice that more efficiently binds cell-surface transferrin receptor (TfR) and is also capable of conveniently loading cargoes for targeted transmembrane delivery.…”
mentioning
confidence: 99%
“…Toward this end, here we tested the performance of the G4PA nanodevice for targeted delivery of nucleic acid cargoes, with a commonly used commercial transfection agent, lipo3000, as the control nanodevice. Here Hela cells are used as the target and 293T cells with low-expressed TfR , as the negative control. Figure a shows that the sulfo-Cy5-labeled DNA cargo can be efficiently transported by lipo3000 into both the target and the control cells, indicating the lack of targeting ability of conventional liposome transfection.…”
mentioning
confidence: 99%
“…The utility of this phase-changing strategy was then examined by synthesizing a bivalent Sgc8c-Sgc8c glue (AptG-5) and a trivalent Sgc8c-Sgc8c-Sgc8c glue (AptG-6) to perform specific cancer cell recognition at low concentration levels . Noteworthily, AptG-6 was tailored efficiently in a one-pot reaction operation under the optimized bioconjugation conditions with 2 equiv of Sgc8c-N 3 and 1 equiv of DBCO-Sgc8c-DBCO aptamers in a sample tube and reacted for 1 h at −20 °C (Figure S4).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The utility of this phase-changing strategy was then examined by synthesizing a bivalent Sgc8c-Sgc8c glue (AptG-5) and a trivalent Sgc8c-Sgc8c-Sgc8c glue (AptG-6) to perform specific cancer cell recognition at low concentration levels. 23 Noteworthily, AptG-6 was tailored efficiently in a one-pot reaction operation under the optimized bioconjugation conditions with 2 equiv of Sgc8c-N 3 and 1 equiv of DBCO-Sgc8c-DBCO aptamers in a sample tube and reacted for 1 h at −20 °C (Figure S4). Considering the importance of the stability of aptamers in specific cancer cell recognition applications, the stability of Sgc8c, AptG-5, and AptG-6 were compared, and it was found that AptG-6 (24 h) was much more stable than AptG-5 (12 h) and Sgc8c (6 h) against 10% fetal bovine serum (FBS) (Figure 4a).…”
Section: Development Of Molecule Stacking Strategymentioning
confidence: 99%
“…One major challenge lies in the susceptibility of FNAs to degradation by ubiquitous nucleases in biological systems, which limits their practical applications. Considerable effort has been devoted to improving the biostability of nucleic acids by modifying the phosphate backbone, sugar structure, , nucleobase, and creating circular structures to prevent the formation of free ends. On the other hand, it is important to consider the potential side effects of modified nucleic acids, even with enhanced resistance against nucleases.…”
Section: Prospectmentioning
confidence: 99%